(untitled) (UNWE Yearbook, 2024)
The use of renewable energy sources is an important aspect of economic development throughout the world, including Europe, as it provides clean energy and contributes significantly to environmental transformation. Three clusters of EU countries are identified concerning their progress of the share of renewable energy (SRE) use in gross energy consumption for 2004-2022 applying cluster analysis based on the SRE trends in the period. Effects of important factors for expanding SRE are analyzed by developing a set of econometric models of renewable energy use in main sectors of energy balance – electricity, transport and cooling & heating.